2016
DOI: 10.1098/rstb.2015.0412
|View full text |Cite
|
Sign up to set email alerts
|

Left–right leaf asymmetry in decussate and distichous phyllotactic systems

Abstract: One contribution of 17 to a theme issue 'Provocative questions in left -right asymmetry'. Leaves in plants with spiral phyllotaxy exhibit directional asymmetries, such that all the leaves originating from a meristem of a particular chirality are similarly asymmetric relative to each other. Models of auxin flux capable of recapitulating spiral phyllotaxis predict handed auxin asymmetries in initiating leaf primordia with empirically verifiable effects on superficially bilaterally symmetric leaves. Here, we exte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Furthermore, Dhkar and Pareek (2014) affirmed that besides genetic control, environmental factors (mainly temperature and light) have significant contributions in the final adjustment of the shape of the leaf. Martinez et al (2016) reported that plastic properties of leaf shape are caused by variation in lamina growth At the population level, PPI value ranged from 0.41 to 0.51, and the mean value was 0.47. The lowest PPI value is observed in the Rumbio population (0.41), followed by the Sentajo population (0.43), while the highest PPI value is observed in the Lingga-1 population (0.51).…”
Section: Phenotypic Plasticity Indexmentioning
confidence: 99%
“…Furthermore, Dhkar and Pareek (2014) affirmed that besides genetic control, environmental factors (mainly temperature and light) have significant contributions in the final adjustment of the shape of the leaf. Martinez et al (2016) reported that plastic properties of leaf shape are caused by variation in lamina growth At the population level, PPI value ranged from 0.41 to 0.51, and the mean value was 0.47. The lowest PPI value is observed in the Rumbio population (0.41), followed by the Sentajo population (0.43), while the highest PPI value is observed in the Lingga-1 population (0.51).…”
Section: Phenotypic Plasticity Indexmentioning
confidence: 99%
“…S12D). When ADD was set to promote the growth of only one side of the primordium, organs with oblique, bilaterally asymmetrical bases, like the ventral (rather than dorsal or lateral) sepals of Delphinium and leaves of Begonia (Begoniaceae) ( 33 ), were generated (fig. S12, E and F).…”
Section: Resultsmentioning
confidence: 99%
“…In spiral systems, the peak of auxin concentration is displaced towards the descending side of the center of mass of leaf primordia and is influenced by architecture of the shoot apical meristem, as observed in tomato (Déb, Marti, Frenz, Kuhlemeier, & Reinhardt, 2015). Studies on Vitis spp and Hedera helix showed that the asymmetric flux of auxin in the shoot apical meristem accentuates differences along the left-right axis and is influenced by phyllotaxis (Martinez, Chitwood, Smith, & Sinha, 2016).…”
Section: Discussionmentioning
confidence: 97%